Challenges of the continuous hairpin technology for production techniques. (March 2023) - Kampker, Achim; Heimes, Heiner Hans; Dorn, Benjamin; Brans, Florian; Stäck, Christian
Abstract: In the electrification of the automotive drive train, an unprecedented change is currently influencing the production technology of stators. Previously established round wire winding technologies are being replaced by windings made of thick rectangular conductors specially tailored to the requirements of mobile electric traction. A cascading technology development from the I-pin to the currently established U-hairpin technology can be observed. Continuous hairpin technology (CHP), also known as wave winding or S-wind, is increasingly under investigation of the industrial sector. In this winding technology, solid, usually, rectangular conductors are continuously inserted into a lamination stack. Decisive product and production advantages are found in the leaner production process chain, the reduced winding head heights and contact points. However, numerous design and process limitations are also associated with this winding technology. This paper describes the process chain of continuous hairpin technology, identifies process limitations and points out challenges and approaches for future production technology.